Kompetensi Pustakawan Layanan Referensi di Masa Depan - Ratu Syifa Alrissa (Pustabiblia: Journal of Library and Information Science, 2024)
Reference services in libraries and reference librarians are two things that cannot be separated in practice. Reference services are one of the activities as well as a forum for providing information in information institutions, such as libraries. Reference librarians have a very important role in providing reference services at library information institutions, librarians with competent qualifications are needed to be able to create optimal quality reference services.Basically the form of a reference service is finding information to answer specific questions, helping users find appropriate information, and forbidding users from using library information sources according to their use. The existence of a commitment to reference services makes a major contribution to users in obtaining the information they need. The unstoppable development of technology and knowledge has increasingly encouraged reference librarians to fulfill the various competencies required due to the large amount of information circulating. This study aims to find out what competencies librarians for reference services or reference librarians must have and for what innovations librarians can make in providing their services through observation, which is a way to be able to gather information in accordance with what is sought through observation. Based on the research conducted, it can be seen that reference librarians have an important role in providing reference services, both in finding, managing, and presenting information to information users according to their needs.